MEKANISME PENGAWASAN BADAN INTELIJEN NEGARA REPUBLIK INDONESIA DALAM KERANGKA HUKUM YANG DEMOKRATIS - Muslim, Mutia Jawaz; Fikrina, Aulia (Lembaga Marwah Rakyat, 2024)
Indonesia is a country that is very diverse in various aspects of life so there are big threats to its defense and security. Intelligence is needed as an initial gateway in providing information and recommendations to stakeholders to create strategic policies. In a democratic state, the existence of state intelligence must uphold legal principles and human rights. Moreover, in a post-authoritarian country like Indonesia, intelligence is often used as a tool to perpetuate power under the guise of national security. The dark history of past intelligence practices has made this country learn to better organize its functions and authority so that supervision becomes absolutely necessary. This research was conducted using normative juridical methods. The results of this research are (1) the supervisory mechanism regulated in Law Number 17 of 2011 concerning State Intelligence stipulates that there is layered supervision starting from the internal leadership of each intelligence service, then the president as chief executive, the intelligence supervision commission formed by the DPR RI , and civil society. (2) Even though the instrument has well regulated forms of supervision of intelligence, in practice it is still not optimal due to various obstacles